Pengembangan Kurikulum Berbasis Kompetensi Untuk Meningkatkan Kualitas Pendidikan - Lukman Agung; Achmad Junaedi Sitika; Jeani Rida Dwi Lestari; Kharismasita Viska Putri; Muszalika Azahra; Nisa Ulviyah; Yusuf Sutejo (Peneliti.net, 2023)
In an effort to improve the quality of education, the procurement of curriculum development is a necessity, because the curriculum is the pias well as the direction of implementing education in schools. The world of education is required to be able to produce skilled workers who are able to be active and able to be directly involved in global developments. To meet the demands of these developments, reforming and updating the various components of education, especially the educational curriculum, is an urgent thing to do, because in reality the curriculum that is not in accordance with increasingly advanced situations and conditions is no longer relevant to deliver students to be able to compete by treading developments. For this reason, the government through the Ministry of National Education in the 2004/2005 academic year implemented a new curriculum called the Competency-Based Curriculum (CBC). Through various assessments and careful planning, it is hoped that this KBK will be able to produce quality human resources and be able to respond to the global challenges of society.